2020
DOI: 10.3748/wjg.v26.i45.7204
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis index-based nomograms for identifying esophageal varices in patients with chronic hepatitis B related cirrhosis

Abstract: BACKGROUND Esophageal varices (EV) are the most fatal complication of chronic hepatitis B (CHB) related cirrhosis. The prognosis is poor, especially after the first upper gastrointestinal hemorrhage. AIM To construct nomograms to predict the risk and severity of EV in patients with CHB related cirrhosis. METHODS Between 2016 and 2018, the patients with CHB related cirrhosis were recruited and divided into a training or validation cohort at Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Liver fibrosis is a kind of common liver disease, which is mainly caused by the hyperplasia and deposition of extracellular matrix (ECM) resulting from hepatic stellate cell (HSC) activation, as well as an imbalance between ECM synthesis and degradation ( 6 , 7 ). HSC activation and hyperplasia are the central links in the occurrence and development of liver fibrosis ( 8 ), and suppressing HSC activation is the key to the prevention and treatment of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Liver fibrosis is a kind of common liver disease, which is mainly caused by the hyperplasia and deposition of extracellular matrix (ECM) resulting from hepatic stellate cell (HSC) activation, as well as an imbalance between ECM synthesis and degradation ( 6 , 7 ). HSC activation and hyperplasia are the central links in the occurrence and development of liver fibrosis ( 8 ), and suppressing HSC activation is the key to the prevention and treatment of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are many studies on EGV in cirrhosis. The main predictors include PLT count, INR, gallbladder wall thickness, spleen diameter and liver fibrosis index, AAR, FIB-4, APRI and AARPRI [5,8–11,15,16]. These indicators showed good predictive efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination is the "gold standard" for diagnosing and evaluating cirrhosis [7]; nonetheless, this type of examination requires a collection of tissue (liver biopsy), which is an invasive procedure. On the other hand, other non-invasive methods such as imaging methods, elastography techniques, and serum biomarkers based on laboratory tests have shown moderate diagnostic accuracy in assessing portal hypertension of HBV-related cirrhosis [8][9][10][11][12]. Furthermore, studies have shown the potential diagnostic value of metabolic biomarkers in differentiating advanced liver fibrosis or hepatocellular carcinoma from chronic hepatitis B virus (CHB) or HBVrelated cirrhosis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%